PERUBAHAN PENGGUNAAN LAHAN DAN KONVERSI SAWAH DI KAWASAN PERI-URBAN: STUDI KASUS KECAMATAN SOMBA OPU - Sukri, Irwansyah; Arfan, Amal; Muhammad, Fadil; Uzrah, Jaiysul; Suciana, Annisa; Aulia, Wulan (Jurnal Environmental Science, 2025)
Land conversion in peri-urban areas has become an increasingly critical issue as rapid population growth and urban expansion intensify pressure on agricultural land. This study aims to analyze land use change in Somba Opu District from 2014 to 2024 and identify the driving factors and implications of this transformation. A spatial analysis approach using GIS was employed to map and quantify land cover change, supported by field observations and secondary data to interpret the socio-economic and environmental dimensions. Results show a substantial shift from agricultural land to built-up areas: built-up land increased by 291.03 ha, whereas rice fields declined by 612.12 ha over the ten-year period. These patterns reflect strong urbanization pressures driven by population growth, strategic location near Makassar City, limited farmer regeneration, and climate-related crop failures. The decline of agricultural land has reduced local food production capacity, contributed to land degradation, and created unequal economic outcomes among farming communities. The study highlights the urgency of evidence-based spatial planning and adaptive agricultural strategies to mitigate further loss of productive land. The findings contribute to broader knowledge on peri-urban land transformation and emphasize the need for long-term monitoring and policy interventions that prioritize environmental balance and community welfare.